The Principle of Mubādalah in Islamic Family Law: A Functional Sociological Approach to Reducing Domestic Conflict - Hafis, Muhammad; Nurriyanto, Eko Wahyudi; Nelli, Jumni; Syafitri, Juliani; Rafia’aturrahmah (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
Abstract: Domestic conflicts often stem from gender inequality, which triggers role tensions, communication dysfunction, and violence. This study analyzes the relevance of the concept of mubādalah (the principle of reciprocity) in Islamic family law as a structural-functional solution for building domestic harmony. Through a qualitative approach using library research methods, this study integrates the analysis of Islamic texts (the Qur'an, hadith, Indonesian positive law) and family sociology theory. The results show that: First, the concept of mubādalah is manifested in five operational pillars: (1) shared responsibility (mitsāqan ghalīẓan), (2) husband-wife partnership (zawj), (3) proper social interaction (mu‘āsharah bil ma‘rūf), (4) dialogue (tasyāwur), and (5) mutual affection (tahābub). Second, these pillars reconstruct gender relations through mutuality, thereby overcoming conflicts caused by injustice. Third, the sociological perspective of the family confirms mubādalah as an adaptive mechanism, whereby role flexibility strengthens household resilience in the face of socioeconomic change. This study concludes that mubādalah is not only a normative framework, but also a practical solution for Muslim couples to achieve equal and substantive household harmony. Keywords: Mubādalah, Family Law, Gender, Functional Sociology, Conflict.   Abstrak: Konflik rumah tangga sering kali berakar dari ketidakadilan gender yang memicu ketegangan peran, disfungsi komunikasi, dan kekerasan. Studi ini menganalisis relevansi konsep mubādalah (prinsip kesalingan) dalam hukum keluarga Islam sebagai solusi struktural-fungsional untuk membangun keharmonisan rumah tangga. Melalui pendekatan kualitatif dengan metode penelitian kepustakaan, penelitian ini mengintegrasikan analisis teks-teks Islam (Al-Qur'an, hadis, hukum positif Indonesia) dan teori sosiologi keluarga. Hasil penelitian menunjukkan bahwa: Pertama, konsep mubādalah termanifestasi dalam lima pilar operasional: (1) tanggung jawab bersama (mitsāqan ghalīẓan), (2) kemitraan suami-istri (zawj), (3) pergaulan yang patut (mu‘āsharah bil ma‘rūf), (4) dialog (tasyāwur), dan (5) kasih sayang timbal balik (tahābub). Kedua, pilar-pilar ini merekonstruksi hubungan gender melalui mutualitas, sehingga mengatasi konflik yang ditimbulkan oleh ketidakadilan. Ketiga, perspektif sosiologi keluarga mengonfirmasi mubādalah sebagai mekanisme adaptif, dimana fleksibilitas peran memperkuat ketahanan rumah tangga menghadapi perubahan sosioekonomi. Studi ini menyimpulkan mubādalah bukan hanya sebagai kerangka normatif, tetapi juga sebagai solusi praktis bagi pasangan Muslim untuk mewujudkan keharmonisan rumah tangga yang setara dan substantif. Kata Kunci: Mubādalah, Hukum Keluarga, Gender, Sosiologi Fungsional, Konflik.